1974
DOI: 10.1128/jb.120.1.253-265.1974
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Rifampin-Resistant and Streptolydigin-Resistant Mutants of Bacillus subtilis with Altered Sporulation Properties

Abstract: Mutants of Bacillus subtilis with altered deoxyribonucleic-dependent ribonucleic acid polymerase activity have been isolated and characterized. These mutants, selected as strains resistant to rifampin or streptolydigin, demonstrate drug-resistant in vitro ribonucleic acid synthesis. Sporeforming ability and support of phage infection are altered in many of the mutants. Mutations to rifampin and streptolydigin resistance have been located on the B. subtilis chromosome and ordered relative to the markers cysA14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…Analysis of these cultures then showed that oligosporogenous (Spo'l-) organisms had arisen at a mean frequency of 1.8 x Following mutagenesis of suspensions of SBA52 by treatment with M N N G or EMS as described by Bowring & Morris (1985), attempts were made to select mutant strains displaying all possible combinations of loss of the three phenotypic traits of Spo, Gran and Soh. Sporulation mutants were isolated both by screening visually for their characteristic colony morphology and by selecting for rifampicin resistance (Sonenshein et al 1974). Colonies of mutants defective in granulose synthesis were identified by their non-reaction with I, vapour (Robson et al 1974) and colonies of non-solventogenic mutants were identified by their colour reaction in the tetrazolium blue test procedure.…”
Section: P R O P E R T I E S O F M U T a N T S D E R I V E D From S Tmentioning
confidence: 99%
“…Analysis of these cultures then showed that oligosporogenous (Spo'l-) organisms had arisen at a mean frequency of 1.8 x Following mutagenesis of suspensions of SBA52 by treatment with M N N G or EMS as described by Bowring & Morris (1985), attempts were made to select mutant strains displaying all possible combinations of loss of the three phenotypic traits of Spo, Gran and Soh. Sporulation mutants were isolated both by screening visually for their characteristic colony morphology and by selecting for rifampicin resistance (Sonenshein et al 1974). Colonies of mutants defective in granulose synthesis were identified by their non-reaction with I, vapour (Robson et al 1974) and colonies of non-solventogenic mutants were identified by their colour reaction in the tetrazolium blue test procedure.…”
Section: P R O P E R T I E S O F M U T a N T S D E R I V E D From S Tmentioning
confidence: 99%
“…Mutants blocked after stage 0, i.e., stages II, m, and IV, produced a modified RNA polymerase and secreted normal quantities of serine protease and esterase. Sonensheim et al (299) isolated a large number of rifampin and streptolydigin-resistant mutants of B. subtilis, many of which were blocked at stage 0. The authors concluded that only those strains that sporulated less well than their parents were deranged for protease synthesis.…”
Section: Regulation Of Synthesismentioning
confidence: 99%
“…Bacteria and phage. B. subtilis 3610 (ATCC 6051) (23) and M021, a rifampin-resistant mutant of strain 168 (3,22), and wild-type phage 0e (23) have been described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Subtilis initiation medium (SIM) was a slight modification of a medium described by Torriani et al (27) and contained: tris(hydroxymethyl)aminomethane-hydrochloride (pH 7.4), 0.1 M; KCl, 10 mg/ml; L-alanine, 0.34 mg/ml; and glucose, 2 mg/ml. Nutrient sporulation medium DSM (22), L broth, L agar, top agar, and media 121A and 121B (23) have been described previously.…”
Section: Methodsmentioning
confidence: 99%